The TORC2 component, Sin1, controls migration of anterior mesendoderm during zebrafish gastrulation. - Julien G Dumortier; Nicolas B David (PLoS ONE)
TORC2 is a serine-threonine kinase complex conserved through evolution that recently emerged as a new regulator of actin dynamics and cell migration. However, knockout in mice of its core components Sin1 and Rictor is embryonic lethal, which has limited in vivo analyses. Here, we analysed TORC2 function during early zebrafish development, using a morpholino-mediated loss of function of sin1. Sin1 appears required during gastrulation for migration of the prechordal plate, the anterior most mesoderm. In absence of Sin1, cells migrate both slower and less persistently, which can be correlated to a reduction in actin-rich protrusions and a randomisation of the remaining protrusions. These results demonstrate that, as established in vitro, the TORC2 component Sin1 controls actin dynamics and cell migration in vivo. We furthermore establish that Sin1 is required for protrusion formation downstream of PI3K, and is acting upstream of the GTPase Rac1, since expression of an activated form of Rac1 is sufficient to rescue sin1 loss of function.